Investigation by HSRC - G. Cilliers (AOSIS, 1983)
At the request of the former Department of Health, a survey was made of the manpower in health and welfare services in the RSA in 1981. The aim of this investigation was to obtain a picture of the institutions rendering health and welfare services, the facilities available and the manpower involved in these services. During the past two decades much attention has been devoted to the availability of educated manpower in all fields of the labour market. The general shortage of highly skilled manpower is also experienced in the health fields and necessitates better utilisation of the available manpower.